Reimagining New Approaches in Teacher Professional Development - Petrus Mahlangu, Vimbi (IntechOpen, 2018)
Reimagining new approaches in teacher professional development is the focus of this book. It looks at different perspectives of teacher professional development. Most chapters directly or indirectly present and discuss new approaches in teacher professional development in general. The purpose of the book is to inform readers that there are new ways of developing teachers professionally, and to equip readers with the skills needed to teach or behave in a professional manner. The book aims at providing new knowledge about professional development to academics, universities, education authorities, teachers, parents, and governing body members. The authors have diverse perspectives about the issues or aspects pertaining to teacher professional development.